2022
DOI: 10.3390/cells11182791
|View full text |Cite
|
Sign up to set email alerts
|

From Molecular Mechanisms to Therapeutics: Understanding MicroRNA-21 in Cancer

Abstract: MicroRNAs (miRNAs) are small noncoding RNAs that play an important role in regulating gene expression at a posttranscriptional level. As one of the first discovered oncogenic miRNAs, microRNA-21 (miR-21) has been highlighted for its critical role in cancers, such as glioblastoma, pancreatic adenocarcinoma, non-small cell lung cancer, and many others. MiR-21 targets many vital components in a wide range of cancers and acts on various cellular processes ranging from cancer stemness to cell death. Expression of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 158 publications
(139 reference statements)
0
27
0
Order By: Relevance
“…MiR-21, strongly upregulated in aggressive gastric cancer, triggers cell proliferation, invasion, and migration by remodeling the extracellular matrix and downmodulating key apoptotic genes like the tumor suppressor RECK. 24 MiR-192 and miR-215 can promote cell proliferation and migration, via APC inhibition and the Wnt signaling activation, thus inducing gastric cancer progression. 25 MiR-1275 regulates gastric cancer cell lipid signaling by reverting the oncogenic effects mediated by fatty acid amide hydrolase, through the downregulation of arachidonoyl ethanolamide (AEA)/lysophosphatidic acid (LPA) signaling and activation of the cyclooxygenase-2 (COX-2)/prostaglandin E2 (PGE2) axis, thereby affecting gastric cancer progression.…”
Section: Mirnas: Emerging Targets For Cancer Treatmentmentioning
confidence: 99%
“…MiR-21, strongly upregulated in aggressive gastric cancer, triggers cell proliferation, invasion, and migration by remodeling the extracellular matrix and downmodulating key apoptotic genes like the tumor suppressor RECK. 24 MiR-192 and miR-215 can promote cell proliferation and migration, via APC inhibition and the Wnt signaling activation, thus inducing gastric cancer progression. 25 MiR-1275 regulates gastric cancer cell lipid signaling by reverting the oncogenic effects mediated by fatty acid amide hydrolase, through the downregulation of arachidonoyl ethanolamide (AEA)/lysophosphatidic acid (LPA) signaling and activation of the cyclooxygenase-2 (COX-2)/prostaglandin E2 (PGE2) axis, thereby affecting gastric cancer progression.…”
Section: Mirnas: Emerging Targets For Cancer Treatmentmentioning
confidence: 99%
“…MiR-21 is one of cancer research’s first identified “miRNA enhancers” ( 32 ). All cells in the human body can produce extracellular vesicles (EVs), which are membranous vesicles released into the extracellular matrix.…”
Section: Ncrnas and Nsclcmentioning
confidence: 99%
“…MiR-21 was significantly higher in sputum and plasma samples from patients with NSCLC than healthy donors. Thus, in addition to promoting growth and invasion phenotypes, miR-21 is a non-invasive biomarker for NSCLC diagnosis ( 32 , 34 ). Recent studies have focused on the combined effects of let-7 and miR-21.…”
Section: Ncrnas and Nsclcmentioning
confidence: 99%
“… 83 MiR-21 is considered as an oncogenic effect in different tumors, and its overexpression can promote solid tumor development. 84 Thus, miR-21 inhibition may reduce fibrosis and suppress populations of immunosuppressive cells simultaneously, thereby slowing premalignant progression and shrinking the tumors. 85 Overall, M2-TAMs-Exos-ncRNAs are essential for tumor growth, development, and in drug resistance.…”
Section: Role Of M2-exos-ncrnas In the Pathogenesis Of Different Gic ...mentioning
confidence: 99%